2013
DOI: 10.1080/00207594.2012.696651
|View full text |Cite
|
Sign up to set email alerts
|

The dimensional structure of people's fears, threats, and concerns and their relationship with right‐wing authoritarianism and social dominance orientation

Abstract: Most theories addressing the topic have proposed that threat and fear underlie right-wing authoritarianism (RWA), and many empirical findings have been consistent with this proposition. Important questions, however, remain unanswered, such as whether RWA is associated with fear and threat in general or only specific kinds of fear and threat. Theories of RWA generate markedly different predictions on this issue, particularly with respect to social or personal fears, and whether the association would also hold f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
47
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 39 publications
(69 reference statements)
7
47
0
Order By: Relevance
“…RWA also predicts perceiving greater “external”—mainly social—threats longitudinally (Onraet, Dhont, & Van Hiel, ). Cross‐sectional studies have similarly noted a positive link between RWA and fear‐based threats (e.g., Shaffer & Duckitt, ). Relatedly, researchers have studied ideology and risk perception, finding that higher RWA is associated with perceiving potentially precarious social and ethical situations as riskier (Choma & Hodson, ) and rating everyday (e.g., vaccinations) and voluntary (e.g., drinking alcohol) hazards for the self as riskier (Choma, Hanoch, Gummerum, & Hodson, ).…”
Section: Collective Actionmentioning
confidence: 92%
See 1 more Smart Citation
“…RWA also predicts perceiving greater “external”—mainly social—threats longitudinally (Onraet, Dhont, & Van Hiel, ). Cross‐sectional studies have similarly noted a positive link between RWA and fear‐based threats (e.g., Shaffer & Duckitt, ). Relatedly, researchers have studied ideology and risk perception, finding that higher RWA is associated with perceiving potentially precarious social and ethical situations as riskier (Choma & Hodson, ) and rating everyday (e.g., vaccinations) and voluntary (e.g., drinking alcohol) hazards for the self as riskier (Choma, Hanoch, Gummerum, & Hodson, ).…”
Section: Collective Actionmentioning
confidence: 92%
“…The story for SDO is more nuanced, with SDO being unrelated or related negatively to threat. For instance, SDO is generally unrelated to perceptions of the world as a dangerous place (Perry et al, 2013), external social threats (Onraet, Van Hiel, Dhont, & Pattyn, 2013;Shaffer & Duckitt, 2013), risky social or ethical situations (Choma & Hodson, 2017), and everyday or voluntary hazards (Choma et al, 2013), and associated negatively with threat or perceiving risk. For example, those higher in SDO rate health (e.g., firefighting, mountain climbing) and competitive hazards (e.g., highrisk investment) as less risky (Choma et al, 2013) and perceive potentially dangerous recreational and health situations as less precarious (Choma & Hodson, 2017).…”
Section: Ideologymentioning
confidence: 99%
“…In order to explore the causes of the different threat types, we investigated the associations between threat types, intergroup contact experiences and individual differences. Research has shown that negative intergroup contact (e.g., Barlow et al, 2012), national identification (e.g., Louis, Esses, & Lalonde, 2013), right-wing authoritarianism, social dominance orientation (e.g., Shaffer & Duckitt, 2013), and zero-sum beliefs (e.g., Cohrs & Asbrock, 2009) are positively associated with intergroup threat. Reversely, positive contact (e.g., Barlow et al, 2012) and pro-diversity beliefs (e.g., Kauff, Stegmann, van Dick, Beierlein, & Christ, 2018) are negatively associated with intergroup threat.…”
Section: S Tudymentioning
confidence: 99%
“…The papers in this special section share some assumptions. First, they rely primarily on the concept of RWA as an empirical measure of authoritarianism, although this is complemented by more specific authoritarian reactions (Asbrock & Fritsche, 2013 this issue), social dominance orientation (SDO; Pratto, Sidanius, Stallworth, & Malle, 1994) (Onraet & Van Hiel, 2013 this issue;Shaffer & Duckitt, 2013 this issue), and racist attitudes (Onraet & Van Hiel, 2013 this issue). Second, all the papers rest on the assumption that perceived threat is a cause of RWA.…”
Section: Whatever Happened To the Authoritarian Disposition?mentioning
confidence: 99%